Comparison of gene expression responses of zebrafish larvae to Vibrio parahaemolyticus infection by static immersion and caudal vein microinjection - Xinya Guo; Ce Ji; Xuan Du; Jianfeng Ren; Yao Zu; Weiming Li; Qinghua Zhang (Aquaculture and Fisheries, 2021)
The innate immune response can be activated by infection via different routes. Zebrafish provide a useful infection model for studying inflammation and the innate immune response. We investigated the genes and signaling pathways activated by static immersion and caudal vein microinjection infection using transcriptome profiling and reverse-transcription quantitative PCR (RT-qPCR) to compare the innate immune response in 3 days post-fertilization (dpf) zebrafish larvae infected by Vibrio parahaemolyticus Vp13 strain. The median lethal dose (LD50) values at 96 h following immersion and microinjection were 3.63 × 107 CFU/mL and 5.76 × 102 CFU/nL, respectively. An innate immune response was initiated after 2 h of incubation with the respective LD50 for each infection method. Six hundred and two genes in the immersion group and 359 genes in the microinjection group were activated and differentially expressed post-infection. Sixty-three Gene Ontology (GO) terms and four Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways were significantly enriched in the immersion group, compared with only three GO terms and no KEGG pathways in the microinjection group. Two genes, tnfb and ccl20a.3, were significantly up-regulated in both groups. We speculated that immersion infection may affect initial dorsal determination, cytochromes, and fatty acid-binding proteins, as well as inflammation, while microinjection infection may mainly directly affect the immune response. Infection with doses > LD50 (1.09 × 109 CFU/mL and 1.09 × 103 CFU/nL by immersion and microinjection, respectively) caused more significant up-regulation of il11a, tnfa, tnfb, il1b, ccl34a.4, ccl20a.3, irak3, cxcl18b, and ccl35.1, suggesting that in addition to the classical innate immunity genes tnfa, tnfb, il1b, and il6, the genes il11a, ccl34a.4, ccl20a.3, cxcl18b, and ccl35.1 were also important for defending against Vp13 infection. These findings highlight the genes involved in the responses of zebrafish to Vp13 infection via different routes and doses, and thus provide the basis for further analyses of immune response signaling pathways.